THE INFLUENCE OF LEADERSHIP, REMUNERATION, AND WORK MOTIVATION ON THE PERFORMANCE OF EMPLOYEES OF YOGYAKARTA ISLAMIC HOSPITAL PDHI - Karnadi Karnadi; Abdul Choliq Hidayat; Salamatun Asakdiyah (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
This study aims to determine the influence of Leadership, Remuneration, and Work Motivation on employee performance at Yogyakarta Islamic Hospital PDHI (RSIY PDHI). The population of this study was employees at RSIY PDHI. Technical sample measurement using the Slovin formula. The sample in this study was 84 employees at RSIY PDHI. Proportional stratified random sampling technique in order to obtain the number of samples from each work unit proportionally as a data collection method. The results showed that Leadership has a positive and significant effect on employee performance, Remuneration has a positive and significant effect on employee performance, and Work Motivation has a positive and significant effect on employee performance. The three variables, namely Leadership, Remuneration, and Work Motivation, simultaneously or simultaneously have a positive and significant effect on employee performance at RSIY PDHI.